Hubungan Peran Pengawas Menelan Obat (PMO) Terhadap Keberhasilan Pengobatan Tuberkulosis Di Puskesmas Kecamatan Johar Baru Jakarta Pusat Tahun 2016 - Wahyuni Herda; Insan Sosiawan A Tunru; Yusnita Yusnita (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2018)
Tuberculosis is a disease of global concern. By 2015 six countries contributing to 60% of the global total are India, Indonesia, China, Nigeria, Pakistan and South Africa. China, India and Indonesia alone accounted for 45% of cases in the world.The World Health Organization (WHO)has recommended the Directly Observed Treatment Shortcourse (DOTS) strategy for TB control by involving Drug Supervisors (PMO). It aims to achieve patient recovery, prevent transmission, and avoid drug resistant cases. This study aims to determine the relation between the roles of treatment observers (PMO) with the success of tuberculosis treatment at community health center of Johar Baru Central Jakarta in 2016.This research was conducted by Cross-Sectional non-experimental quantitative method. Population and sample are the patient of adult pulmonary and extrapulmonary tuberculosis at community health center of Johar Baru Central Jakarta in 2016. Samples are selected by using Simple Random Sampling. The data were collected by interview using questionnaire. Data analysis using SPSS with Chi-Square test.There were 45 respondents (80,4%) succeed in TB treatment and respondent with PMO roles category were 40 (71,4%). Result of statistical test using Chi-Square test obtained P value = 1,000 (> 0,05).There is no relation between the roles of treatment observers (PMO) with the success of tuberculosis treatment at community health center of Johar Baru Central Jakarta in 2016.